Penguatan Ekosistem Halal di Indonesia 2024 melalui Klinik Halal: Strengthening the Halal Ecosystem in Indonesia 2024 through Halal Clinics - Adenan, Moh; Cholifah, Umi; Wulandari, Deasy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The Prosendi Desa is conducted in the Tegal Besar Village, Kaliwates Sub-district, Jember Regency. It holds substantial potential for developing the halal industry towards achieving the Halal Industry Indonesia 2024. This initiative takes place in the administrative city, primarily due to the heightened concern of MSB operators regarding business legality and halal certification, compared to rural areas in other sub-districts of the Jember Regency. The PRA approach aims to enhance the knowledge of business operators and village government advocates. The Implementation Team, as facilitators, provides direct information, socialization, counseling, and assistance to MSB operators to obtain business legality through the Business Identification Number (NIB) and Halal Certification. The proposed solution consists of two phases/years. The first year encompasses The addition of 10 NIBs for MSB operators as identification, The establishment of a